STUDENTS’ SOCIAL BEHAVIOR, MOTIVATION AND INTEREST IN USING ENGLISH ON INSTAGRAM AT BOSOWA UNIVERSITY - Nur Putri Yanti Daties; Andi Hamzah Fansury (Teaching English as a Foreign Language Overseas Journal, 2022)
The objectives of the research were (1) to find out the influence of Instagram on social behavior in using English of under graduate students (2) To find out the influence of Instagram on student’s motivation in using English and (3) To find out the students interest in using English on Instagram. The researcher applied mixed method namely triangulation mixed method design (QUAN-QUAL). The population of this research was the students of English Language Education Program FKIP Bosowa University Makassar. This research used purposive sampling. The sample of this research consisted of 40 students; 10 students from first semester and 10 students from third Semester, 10 Students from fifth semester and 10 students from seventh semester. The research data were collected by questionnaire which was analyzed by descriptive statistic through SPSS version 16 for windows program. The result of data analysis shown that College students had on social networking like Instagram may affect their social behavior. Instagram can encourage the students' motivation and attitudes towards learning English, and also increase interaction between teachers, students and others. Students’ interest in using English on Instagram. In using Instagram, the students are required to be active in using English to improve their ability